Electrochemical Controlled Supramolecular Switches Formed by Ionic Self-Assembly - Hong Li*, Qiu; Lin Luo, Lin; Zhang, Tao; Wang, Ying; Jie Yan, Xiao; Ting Zhou, Wen; Wang, Fang; Wei Meng, Yong (Asian Journal of Chemistry, 2013)
Controlling aggregates transformations are achieved in this work by electrochemical method without the adding of a third substance. In response to redox stimuli, the self-assembly nanostructures of supramolecular amphiphile formed by ionic self-assembly technique can change between nanowires and vesicles. The transformation of self-assembly aggregates induced by redox reactions were found to be brought out by drastic change in amphiphilicity of the supramolecular complexes due to the oxidation and reduction of a ferrocenyl moiety. The novel finding may be applied in many areas including development of smart materials.